Ultralow Interfacial Thermal Resistance of Graphene Thermal Interface Materials with Surface Metal Liquefaction - Dai, Wen; Ren, Xing‑Jie; Yan, Qingwei; Wang, Shengding; Yang, Mingyang; Lv, Le; Ying, Junfeng; Chen, Lu; Tao, Peidi; Sun, Liwen; Xue, Chen; Yu, Jinhong; et al. (Nano-Micro Letters, 2022)
Developing advanced thermal interface materials (TIMs) to bridge heat-generating chip and heat sink for constructing an efficient heat transfer interface is the key technology to solve the thermal management issue of high-power semiconductor devices. Based on the ultra-high basal-plane thermal conductivity, graphene is an ideal candidate for preparing high-performance TIMs, preferably to form a vertically aligned structure so that the basal-plane of graphene is consistent with the heat transfer direction of TIM. However, the actual interfacial heat transfer efficiency of currently reported vertically aligned graphene TIMs is far from satisfactory. In addition to the fact that the thermal conductivity of the vertically aligned TIMs can be further improved, another critical factor is the limited actual contact area leading to relatively high contact thermal resistance (20–30 K mm2 W−1) of the “solid–solid” mating interface formed by the vertical graphene and the rough chip/heat sink. To solve this common problem faced by vertically aligned graphene, in this work, we combined mechanical orientation and surface modification strategy to construct a three-tiered TIM composed of mainly vertically aligned graphene in the middle and micrometer-thick liquid metal as a cap layer on upper and lower surfaces. Based on rational graphene orientation regulation in the middle tier, the resultant graphene-based TIM exhibited an ultra-high thermal conductivity of 176 W m−1 K−1. Additionally, we demonstrated that the liquid metal cap layer in contact with the chip/heat sink forms a “liquid–solid” mating interface, significantly increasing the effective heat transfer area and giving a low contact thermal conductivity of 4–6 K mm2 W−1 under packaging conditions. This finding provides valuable guidance for the design of high-performance TIMs based on two-dimensional materials and improves the possibility of their practical application in electronic thermal management. Highlights: 1 A three-tiered thermal interface materials was proposed with the through-plane thermal conductivity up to176 W m−1 K−1 and contact thermal resistance as low as 4–6 K mm2 W−1 (double sides). 2 The liquid metal acts as a buffer layer to connect vertically aligned graphene with the rough heater/heat sink, improving effective contact thermal conductance by more than an order of magnitude.